Identification of Middle Mesial Canal in Mandibular Molars Using Five Different Techniques: An In vitro Study - Kanduri Venkata Naga Vamseekrishna; Navneet Kukreja; Mayank Sachdeva; Sindhura Ravi; Swati Chhabra; Surinder Sachdeva (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim: The purpose of the study was to find out the incidence of the middle mesial canal in mandibular molars by using five different techniques. Materials and Methods: A total of 150 extracted human mandibular first molars were selected, and cone beam computed tomography (CBCT) images were taken. Then, conventional access cavities were made, followed by troughing under dental loupes (3X), and were also examined under a dental operating microscope (DOM) (6X). Incidence of intermediate canals was noted from all these stages. Later, these teeth underwent a clearing method procedure, and incidence was noted from this stage and compared. Results: The overall diagnostic accuracy of CBCT (9 mm) had 97.48%, and evaluation under DOM had an overall accuracy of 97.33%. The least accuracy was found with the naked eye (92.67%). Conclusion: This study advocates the usage of newer methods like CBCT and DOM to find out and negotiate these accessory canals.